Pengaruh Stres Kerja, Tekanan Pekerjaan dan Keletihan Kerja terhadap Kinerja Karyawan pada Bank BRI Wilayah Muara Bulian - Etty Siswati; Ratna Ratna (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The aim of this study to know the effect of job stress, job pressure and job fatigue on employee performance at BNK BRI of Muara Bulian Are. Data collecting used survey method, that is to obtain information from respondents by using interview techniques and spreading the list of questions and to measureit by using Likert scale. Population of the research is employees at BANK BRI of Muara Bulian Area. Analyzer used is multiple linear regression, this method using computer assistance through program SPSS 20.0 for windows. From the calculation of SPSS 20.0, it found that is the job stress variable is 2,193, because tcount> from ttable, (2,193> 1.68195 hence Ho accepted and Ha rejected, it means that independent variable has influence to dependent variable, which means there is partial influence between job stress to employees performance at Bank BRI of MuaraBulian Area.Variable job pressure of 0.254, Because tcount<of ttable, (0.254 <1.68195) Ha is accepted and Ho is rejected, it means that independent variable has no influence on dependent variable, meaning there is no partial influence between job pressure on employee performance at Bank BRI of Muara Bulian Area.Job fatigue variable is 9.461 Because to tcount> from ttable, (9.461> 1.68195) then Ha accepted and Ho accepted, Ha rejected means that the independent variable has influence on the dependent variable, which means there is partial influence between job fatigue on employee performance on Bank BRI of Muara Bulian Area.